Studiu privind importanța socializării în cadrul antrenamentelor a copiilor de vârstă pubertară care practică înotul [Articol] - Nedelcu, Răzvan Ioan; Rîșneac, Boris (CEP USM, 2024)
In this article we will highlight the importance of socialization in swimming training and the need to include activities that contribute to the development of social skills and social interactions, but with the mention that the focus on physical and specific training should not be omitted. Improving social skills can help build well-rounded individuals who are able to work in teams, express their thoughts and manage their emotions in a healthy way. The methods used are the sociological survey, the test method, the sociometric test and statistical-mathematical methods. The obtained results show the need to implement some activities that contribute to increasing the socialization level of pubertal children who practice swimming.
STUDY ON THE IMPORTANCE OF SOCIALIZATION WITHIN THE TRAINING OF ADOLESCENT CHILDREN WHO PRACTICE SWIMMING
Keywords: social skills; training; swimming